Consumer perspectives on grab bars: A Canadian national survey of grab bar acceptability in homes - Levine, Iris C.; Lau, Sin-Tung; King, Emily C.; Novak, Alison C. (Frontiers in Public Health, 2022)
Given the prevalence and severity of bathroom falls and injuries across age groups, there is growing interest in policy-level approaches to bathroom fall prevention. Grab bars reduce fall risk during bathing transfers and improve bathing accessibility for adults of all ages and abilities. However, they are frequently absent from bathing environments, even in the homes of individuals who have a specific need for a grab bar. While mandatory bathroom grab bar installation has been suggested, it is unclear whether this would be supported by Canadians. The purpose of this study was to characterize Canadian public perceptions on the installation and use of grab bars in home bathrooms. We surveyed 443 Canadians about whether they currently had a grab bar and their perspectives on grab bar policy. 65.4% of respondents did not have a grab bar. However, 88.5% of respondents would allow a grab bar to be installed in their bathroom at no cost to them, only 11.5% of respondents would object to grab bar installation becoming mandatory in new builds, and 85.6% of respondents would use a grab bar if it were installed in their bathroom. Responses were affected by age (in four groups: 18–39, 40–59, 60–79, and 80+ years), self-reported impairment, and home ownership status. Older adults, respondents who reported having impairments, and home owners were more likely to respond favorably toward grab bars. Based on these results, the majority of Canadians would respond positively to policy mandating bathroom grab bars in new homes.